The Paraventricular Nucleus of the Hypothalamus in Control of Blood Pressure and Blood Pressure Variability - Savić, Bojana; Murphy, David; Japundžić-Žigon, Nina (Frontiers in Physiology, 2022)
The paraventricular nucleus (PVN) is a highly organized structure of the hypothalamus that has a key role in regulating cardiovascular and osmotic homeostasis. Functionally, the PVN is divided into autonomic and neuroendocrine (neurosecretory) compartments, both equally important for maintaining blood pressure (BP) and body fluids in the physiological range. Neurosecretory magnocellular neurons (MCNs) of the PVN are the main source of the hormones vasopressin (VP), responsible for water conservation and hydromineral balance, and oxytocin (OT), involved in parturition and milk ejection during lactation. Further, neurosecretory parvocellular neurons (PCNs) take part in modulation of the hypothalamic-pituitary-adrenal (HPA) axis and stress responses. Additionally, the PVN takes central place in autonomic adjustment of BP to environmental challenges and contributes to its variability (BPV), underpinning the PVN as an autonomic master controller of cardiovascular function. Autonomic PCNs of the PVN modulate sympathetic outflow towards heart, blood vessels and kidneys. These pre-autonomic neurons send projections to the vasomotor nucleus of rostral ventrolateral medulla (RVLM) and to intermediolateral (IML) column of the spinal cord, where postganglionic fibers towards target organs arise, impinging on BPV. Also, PVN PCNs synapse with NTS neurons which are the end-point of baroreceptor primary afferents, thus, enabling the PVN to modify the function of baroreflex. Neuroendocrine and autonomic parts of the PVN are segregated morphologically but they work in concert when the organism is exposed to environmental challenges via somatodendritically released VP and OT by MCNs. Therefore, BP and its variability are highly dependent on the integrative function of the PVN. The purpose of this overview is to address both neuroendocrine and autonomic PVN roles in BP and BPV regulation.